Measured versus predicted postoperative pulmonary function at repeated times up to 1 year after lobectomy. (11th June 2021) - Shibazaki, Takamasa; Mori, Shohei; Harada, Eriko; Shigemori, Rintaro; Kato, Daiki; Matsudaira, Hideki; Hirano, Jun; Ohtsuka, Takashi
Abstract: : OBJECTIVES: Postoperative pulmonary function is difficult to predict accurately, because it changes from the time of the operation and is also affected by various factors. The objective of this study was to assess the accuracy of predicted postoperative forced expiratory volume in 1 s (FEV1) at different postoperative times after lobectomy. METHODS: This retrospective study enrolled 104 patients who underwent lobectomy by video-assisted thoracic surgery. Pulmonary function tests were performed preoperatively and postoperatively at 3, 6 and 12 months. We investigated time-dependent changes in FEV1. In addition, the ratio of measured to predicted postoperative FEV1 calculated by the subsegmental method was evaluated to identify the factors associated with variations in postoperative FEV1. RESULTS: Compared with the predicted postoperative FEV1, the measured postoperative FEV1 was 8% higher at 3 months, 11% higher at 6 months and 13% higher at 12 months. The measured postoperative FEV1 significantly increased from 3 to 6 months ( P = 0.002) and from 6 to 12 months ( P = 0.015) after lobectomy resected lobe, smoking history and body mass index were significant factors associated with the ratio of measured to predicted postoperative FEV1 at 12 months ( P < 0.001, P = 0.036 and P = 0.025, respectively). CONCLUSIONS: Postoperative FEV1 increased up to 12 months after lobectomy by video-assisted thoracic surgery. The predicted postoperative pulmonary function was underestimated after 3 months, particularly after lower lobectomy. Abstract : Pulmonary function is routinely measured before major lung resection, and its representative indices are vital capacity (VC) and forced expiratory volume in 1 s (FEV1).